2018
DOI: 10.1186/s13012-018-0843-5
|View full text |Cite
|
Sign up to set email alerts
|

Middle managers’ role in implementing evidence-based practices in healthcare: a systematic review

Abstract: BackgroundMiddle managers are in a unique position to promote the implementation of evidence-based practices (EBPs) in healthcare organizations, yet knowledge of middle managers’ role in implementation and determinants (e.g., individual-, organizational-, and system-level factors) which influence their role remains fractured, spanning decades and disciplines. To synthesize understanding, we undertook a systematic review of studies of middle managers’ role in healthcare EBP implementation and determinants of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
144
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(162 citation statements)
references
References 37 publications
17
144
1
Order By: Relevance
“…For example, Powell et al () reported that clinicians in organisations with more proficient cultures or more proactive implementation leadership had greater knowledge of EBP. Birken et al () findings noted that the implementation climate would affect the nurse managers’ role in implementing EBP. In reverse, building EBP implementation climate requires nurse managers to disseminate the significance of EBP and promote EBP practice through the policies and reward systems they established (Aarons et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Powell et al () reported that clinicians in organisations with more proficient cultures or more proactive implementation leadership had greater knowledge of EBP. Birken et al () findings noted that the implementation climate would affect the nurse managers’ role in implementing EBP. In reverse, building EBP implementation climate requires nurse managers to disseminate the significance of EBP and promote EBP practice through the policies and reward systems they established (Aarons et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In reverse, building EBP implementation climate requires nurse managers to disseminate the significance of EBP and promote EBP practice through the policies and reward systems they established (Aarons et al, ). Nurse managers play a fundamental role in shaping supportive EBP implementation culture in health care organisations (Birken et al, ). Nurse managers’ attitudes and performance of EBP are related to the EBP implementation climate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrate critical attributes and behaviors of leaders that influence EBP implementation (Aarons, Ehrhart, Farahnak, & Sklar, ; Birken et al, ; Gifford et al, ). For example, Shuman, Liu, and colleagues () suggest that frontline leaders play a key role in creating practice climates that foster and promote EBP implementation.…”
Section: Introductionmentioning
confidence: 96%
“…This complexity should be accounted for and attended to in order to facilitate successful implementation, and develop new knowledge and practice. Within this complexity, factors that affect implementation processes include the physical environment and infrastructure, availability of time and resources, availability of staff training, availability of support, receptiveness of organizational culture, involvement of all stakeholders, demonstrable benefits of the change and empowering leadership [34][35][36][37][38][39].…”
Section: Implementation Of Transformative Digital Health Technologiesmentioning
confidence: 99%